The COSPAR international space weather action teams (ISWAT) initiative: a driving force for the COSPAR space weather roadmap - Maria M. Kuznetsova; Mario M. Bisi; Hermann J. Opgenoorth; Martin A. Reiss; M. Leila Mays; Lucilla Alfonsi; C. Nick Arge; David Barnes; Anna Belehaki; Thomas E. Berger; Amanda Brecht; Sean Bruinsma; et al. (Advances in Space Research, 2026)

Reliable identification of flood-borne deposits in speleothems using magnetic microscopy - Samuel L. Piascik; Roger R. Fu; Nicolás M. Stríkis; Ricardo I.F. Trindade; Julio Cauhy Rodrigues; Francisco W. Cruz; Gelson F. Souza-Junior; Andrea Borsato; Vitor Azevedo; Plinio Jaqueto; Isabel Tamara Pedron; Perri Thaler; et al. (Quaternary Science Reviews, 2025)

Calorie-restriction treatment mitigates the aging in rat liver model - L. Urlandini; A. E. Leonetti; F. Conforti; A. Perri; D. Lofaro; G. Antonucci; M. Mandalà; S. Bossio; S. Di Agostino; V. Rago (Biogerontology, 2025)
The aging process promotes progressive impairment of homeostasis and the increase of the risk of disease and death. A major hallmark of the aging process is the systemic chronic inflammation which strongly contributes to the onset of aging-related diseases. In the liver, the aging condition drives the hepatocytes to develop a metabolic dysfunction-associated steatosis. Caloric restriction (CR) is a remarkable strategy to delay biological aging, occurring through several mechanisms. In this study we aimed to explore, employing an in vivo rat model, the impact of CR on aging-mediated liver inflammation markers. The experiments were performed on 14 male Sprague–Dawley rats (24 months old). At 18 months old, rats were allocated into two groups: the normal diet (ND) group was continued ad libitum diet, and the CR regimen group was fed a diet of the same chow restricted to 60% of the intake. All animals were sacrificed at 24 months old. Compared to the ND group, morphological examination of the liver revealed a lower level of fibrosis in the CR group, concomitantly with a reduced expression of key fibrotic markers, such as collagen I, fibronectin, and αSMA. Furthermore, CR improved the liver oxidative balance, as showed by the increased expression of two scavenging enzymes, SOD1/SOD. Moreover, we reported concomitant reduction of NLRP3 inflammasome signalling. Interestingly, CR significantly improved the signalling of key members of the nutrition-sensitizing affected by aging, AMPK/SIRT1/LKB1. Collectively our findings support the evidence on the metabolic benefits of CR about aging-related liver inflammation, by inducing a morphological improvement that mirrors the decrease in the expression of inflammatory molecular markers.

Assessing potentially toxic elements (PTEs) content in asbestos and related groundwater: A review of the levels detected - A. Bloise; I. Fuoco; G. Vespasiano; F. Parisi; M.F. La Russa; C. Piersante; G. Perri; S. Filicetti; A. Pacella; R. De Rosa; C. Apollaro (Science of The Total Environment, 2024)

Unifying the validation of ambient solar wind models - Martin A. Reiss; Karin Muglach; Richard Mullinix; Maria M. Kuznetsova; Chiu Wiegand; Manuela Temmer; Charles N. Arge; Sergio Dasso; Shing F. Fung; José Juan González-Avilés; Siegfried Gonzi; Lan Jian; et al. (Advances in Space Research, 2023)

Subsistence and complexity of antimicrobial resistance on a community‐wide level - Riccardo Perri; Boris A. Kolvenbach; Philippe F. X. Corvini (Environmental Microbiology, 2020)
Summary There are a multitude of resistance strategies that microbes can apply to avoid inhibition by antimicrobials. One of these strategies is the enzymatic modification of the antibiotic, in a process generally termed inactivation. Furthermore, some microorganisms may not be limited to the mere inactivation of the antimicrobial compounds. They can continue by further enzymatic degradation of the compounds' carbon backbone, taking nutritional and energetic advantage of the former antibiotic. This driving force to harness an additional food source in a complex environment adds another level of complexity to the reasonably well‐understood process of antibiotic resistance proliferation on a single cell level: It brings bioprotection into play at the level of microbial community. Despite the possible implications of a resistant community in a host and a lurking antibiotic failure, knowledge of degradation pathways of antibiotics and their connections is scarce. Currently, it is limited to only a few families of antibiotics (e.g. β‐lactams and sulfonamides). In this article, we discuss the fluctuating nature of the relationship between antibiotic resistance and the biodegradation of antibiotics. This distinction mainly depends on the genetic background of the microbe, as general resistance genes can be recruited to function in a biodegradation pathway.

Females are more proactive, males are more reactive: neural basis of the gender-related speed/accuracy trade-off in visuo-motor tasks - V. Bianco; M. Berchicci; F. Quinzi; R. L. Perri; D. Spinelli; F. Di Russo (Brain Structure and Function, 2020)

Modality-specific sensory readiness for upcoming events revealed by slow cortical potentials - V. Bianco; R. L. Perri; M. Berchicci; F. Quinzi; D. Spinelli; F. Di Russo (Brain Structure and Function, 2020)

Epoxy Resin for the Slope Consolidation Intervention on the Tropea Sandstone Cliff (Southern Calabria, Italy) - F. Ietto; F. Perri; D. Miriello; S. A. Ruffolo; A. Laganà; E. Le Pera (Geoheritage, 2018)

Detectable cerebrospinal fluid JCV DNA in late-presenting HIV-positive patients: beyond progressive multifocal leukoencephalopathy? - S. Mornese Pinna; E. Scarvaglieri; M. G. Milia; D. Imperiale; V. Ghisetti; S. Audagnotto; A. Prochet; F. Lipani; S. Bonora; G. Di Perri; A Calcagno (Journal of NeuroVirology, 2017)

Blood Brain Barrier Impairment in HIV-Positive Naïve and Effectively Treated Patients: Immune Activation Versus Astrocytosis - A. Calcagno; A. Romito; C. Atzori; V. Ghisetti; C. Cardellino; S. Audagnotto; E. Scarvaglieri; F. Lipani; D. Imperiale; G. Di Perri; S. Bonora (Journal of Neuroimmune Pharmacology, 2017)

Prevalence and predictors of blood-brain barrier damage in the HAART era - A. Calcagno; M. C. Alberione; A. Romito; D. Imperiale; V. Ghisetti; S. Audagnotto; F. Lipani; S. Raviolo; G. Di Perri; S. Bonora (Journal of NeuroVirology, 2014)

Heparin and penicillamine–hypotaurine–epinephrine (PHE) solution during bovine in vitro fertilization procedures impair the quality of spermatozoa but improve normal oocyte fecundation and early embryonic development - F. S. Gonçalves; L. S. S. Barretto; R. P. Arruda; S. H. V. Perri; G. Z. Mingoti (In Vitro Cellular & Developmental Biology - Animal, 2014)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Isolation, Identification, Synthesis, and Field Evaluation of the Sex Pheromone of the Brazilian Population of Spodoptera frugiperda - Luciane G. Batista-Pereira; Kathrin Stein; André F. de Paula; Jardel A. Moreira; Ivan Cruz; Maria de Lourdes C. Figueiredo; José Perri; Arlene G. Corrêa (Journal of Chemical Ecology, 2006)

Production of transgenic eggplant (Solanum melongena L.) resistant to Colorado Potato Beetle (Leptinotarsa decemlineata Say) - S. Arpaia; G. Mennella; V. Onofaro; E. Perri; F. Sunseri; G. L. Rotino (Theoretical and Applied Genetics, 1997)